Towards a Global Entrepreneurial Culture: A Systematic Review of the Effectiveness of Entrepreneurship Education Programs - Jacinto Jardim; Ana Bártolo; Andreia Pinho (MDPI AG, 2021)
The number of entrepreneurship education programs (EEP) has increased exponentially over the past two decades. However, a systematic review has not yet been carried out to confirm the effectiveness of EEPs and their presence in the current global world. The main objective of this study was to provide a systematic synthesis of EEP, exploring their characteristics and effectiveness. The search was carried out in the following databases: Scopus, Web of Science, ProQuest, and ERIC. Twenty-nine articles were included, with programs developed mainly in European (n = 15), Asian (n = 6), and American (n = 5) countries. The programs were primarily aimed at higher education students (n = 17), addressing business plans and the development of entrepreneurial skills. However, greater attention is paid to entrepreneurial skills in both primary and secondary education. The development of the programs under analysis varied between one week and two years. The studies showed the effectiveness of most of these programs in promoting entrepreneurial skills at all levels of education. In turn, there was no verified increase in the intention to start a business since this intention is determined by predisposition, namely socio-cultural and family aspects. This systematic review of the EEP points to the need for this type of program to be preferentially developed in the early school years, since it is at that time that predispositions are created for the development of entrepreneurial skills and intentions. This condition is corroborated by the global geography of the EEP, which demonstrates that, where there is currently an entrepreneurial culture, countries have made a long educational journey, with strategic options from the perspective of educational policies defending entrepreneurship among the younger generations.